2019
DOI: 10.1002/ep.13138
|View full text |Cite
|
Sign up to set email alerts
|

Biogasification of Cassava Residue for On‐Site Biofuel Generation for Food Production with Potential Cost Minimization, Health and Environmental Safety Dividends

Abstract: Convenient energy sources like biomethane and electricity are scarce commodities in cassava producing countries that depend on wood and charcoal for energy supply. Combustion of wood and charcoal releases substances that impair human health. In 2016, about 30 million metric tons of cassava peeling residues (CPR) were generated worldwide and discharged into the environment. Apart from deforestation, loss of biodiversity and soil erosion caused by felling vegetation for wood and charcoal recovery, discharge of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…One study subjected cassava peeling residue (CPR) derived from 1000 kg of cassava root to AD. Output biogas provided sufficient energy to process the 1000 kg root into flour, gari, and starch [158]. Biogas canceled the global warming potential of fossil energy otherwise required for the production of these products, hence contributing to climate change mitigation.…”
Section: Production Of Renewable Energymentioning
confidence: 99%
“…One study subjected cassava peeling residue (CPR) derived from 1000 kg of cassava root to AD. Output biogas provided sufficient energy to process the 1000 kg root into flour, gari, and starch [158]. Biogas canceled the global warming potential of fossil energy otherwise required for the production of these products, hence contributing to climate change mitigation.…”
Section: Production Of Renewable Energymentioning
confidence: 99%
“…Some results of the research work on CPR as sole substrate for AD were reported earlier. These included proximate properties (e.g., moisture content, total solids, volatile solids), digester performance characteristics (methane content of biogas, pH, discharge effluent COD), feedstock materials, sampling procedures, analyses [94]. Presented in Table 5 are results of nutrient values of liquid fraction of CPR digestate.…”
Section: Issuesmentioning
confidence: 99%
“…Entretanto a utilização dos resíduos, como a casca e a parte aérea, podem ser viáveis, mostrando-se como matéria-prima para a produção não somente de etanol, mas também de eletricidade, visto que comercialmente é feito uso somente da raiz da mandioca, seja para consumo in natura ou fabricação de farinha ou fécula (Serra et al, 1978;Boog et al, 2007;Pattiya, 2011;Sivamani et al, 2018). Estudos realizados por Aso et al (2019) estabeleceram que resíduos de cascas, provenientes de 1000 kg de raiz de mandioca, podem gerar energia suficiente para processar 1000 kg de mandioca, tornando a cadeia mais sustentável.…”
Section: Cultura Da Mandiocaunclassified